2010
DOI: 10.1111/j.1745-4565.2009.00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Food Tube: Coverage of Food Safety Issues Through Video

Abstract: Food safety in restaurants is an increasing concern among consumers. A primary population segment working in foodservice is receiving food safety information through new media channels such as video social network websites. This research used content analysis to examine the purpose and messages of food safety‐related videos posted to YouTube. A usable sample of 76 videos was identified using “food safety” in the YouTube search function. Results indicate that videos must be artfully developed to attract YouTube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
(28 reference statements)
0
22
0
Order By: Relevance
“…The You Tube video included in this study targeted fresh produce farm workers, was focused and provided relevant farm food safety topics and this may have allowed participants to associate the video to their working environment and scenarios of potential cross contamination that could occur in the field and pack-house. This indicates that videos that are focused and provide one concept per video are important to maintain viewers' interest (Rhoades & Ellis, 2010).…”
Section: Types Of Training Materialsmentioning
confidence: 99%
“…The You Tube video included in this study targeted fresh produce farm workers, was focused and provided relevant farm food safety topics and this may have allowed participants to associate the video to their working environment and scenarios of potential cross contamination that could occur in the field and pack-house. This indicates that videos that are focused and provide one concept per video are important to maintain viewers' interest (Rhoades & Ellis, 2010).…”
Section: Types Of Training Materialsmentioning
confidence: 99%
“…As Rhoades and Ellis (2010) stated, understanding how frames are used in videos is important because these frames can impact how audience members perceive a certain topic. Right to know and human health frames were the most prominent in the sample, present in the majority of the videos.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…This definition is consistent with Goffman's (1974) explanation that individuals use previous experiences to process information. Traditionally in communication research, framing studies have examined news coverage, but the same process can be used when individuals view videos for information (Rhoades & Ellis, 2010). Regarding GMOs, Abbot et al (2001) found the media used frames such as human health, environmental, regulatory, business, and morality.…”
Section: Literature Review/theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Food safety researchers examined 76 food safety-related videos posted to YouTube and found that a large portion of the information to be only moderately credible [7]. Medical researchers reviewed 54 videos that demonstrated cardiopulmonary resuscitation (CPR) technique and found that while most steps of CPR were fairly-well demonstrated -a number of them demonstrated the steps incorrectly [8].…”
mentioning
confidence: 99%